Implementation of Outcome-Based Education to STEM Strand in Pangasinan State University - John Joseph V Zarate; Jessie Glen D Peralta; Vemma Mae R Guinto; Roy C Ferrer (ASEAN Multidisciplinary Research Journal, 2020)
Outcome-Based Education (OBE) has become an integral part in teaching Science, Technology, Mathematics and Engineering (STEM) strand in the Philippines. It is a paradigm shift in the education system that’s changing the way students learn, teachers think and schools measure excellence and success. The research aimed to find out the significant difference between the perception of students and teachers in the level of implementation of Outcome-Based Education of Pangasinan State University-Integrated Laboratory Schools (PSU-ILS)-High School Department in Bayambang Campus during the 1st Semester of A.Y. 2019 - 2020.   Also, the research sought to answer the extent of the manifestation of the following behaviors by the STEM students after their exposure to OBE. The descriptive method of research, frequency count and T-test for significant differences were used in the study. Reliability was analyzed using IBM SPSS version 25. The findings of the study echoed that the level of implementation of Outcome-Based Education (OBE) approach as perceived by Science, Technology, Engineering and Mathematics Students is highly implemented with a composite mean of 3.73. Also, the extent to which effort to implement OBE has influenced certain educational practices in the school is perceived by teachers’ as moderately implemented with the composite mean of 2.83. Lastly, there is a significant difference in students’ and teachers’ perception in the area of the school’s mission statement that reflects a commitment to enable all students to be successful with the computed significance of 0.042 which is lower than 0.05 level of significance. In addition, a significant difference in students’ and teachers’ perception in the staff’s commitment to the written mission statement with the computed significance of 0.046 which is lower than 0.05 level of significance.  Finally, anchoring on the findings, conclusions and recommendations of the study, the administration, principal and teachers are encouraged work collaboratively to further improve the implementation of Outcome-Based Education.